Companhia Mirai de Dança: um estudo acerca dos caminhos do corpo que dança e ensina - RODRIGUES, Angélica do Socorro Monteiro (2021)
This essay provides insight into dance through the Mirai Dance Company and my experiences as a researcher, educator and artist, within the context of Urban Dances, specifically Hip Hop and Waacking. This paper correlates with the concepts and historical definitions of Urban Dances, teaching, poetic and aesthetic, methodology, ideology and practical application. Based on Klauss Vianna, Laban, Edgar Morin, I propose ways to develop a teaching methodology of urban dances, emphasizing dance as a tool for development for a conscious individual. This experience allows the person to become aware of their body, space, time, and others, stimulating the construction of a collaborative collective.